Diversidad y conservación de anfibios y reptiles en un área protegida privada de una región altamente transformada en el sur de Veracruz, México - Aguilar-López, José Luis; Ortiz-Lozada, Liliana; Pelayo-Martínez, Jaime; Mota-Vargas, Claudio; Alarcón-Villegas, Luis Ernesto; Demeneghi-Calatayud, Ana Paulina (Instituto de Ecología, A.C., 2020)
The establishment of Private Protected Areas (PPAs) is one of the strategies for the protection of biodiversity in face to habitat modification in tropical forests; however, its importance in conservation has been poorly evaluated. In this work we estimate the importance of a PPA, known as Área de Protección y Desarrollo de Ceratozamia (APDC) for the conservation of amphibians and reptiles, compared to two other PPAs (Parque Ecológico Jaguaroundi and Parque Ecológico Tuzandepetl) at southern Veracruz, Mexico. The APDC has an area of 100 hectares: 50 ha of tropical deciduous forest and 50 ha of cattle-pasture. The surveys for this study were carried out between 2015 and 2016, which consisted of free search restricted by time (total sampling effort = 768 person-hours). In total, 20 species of amphibians and 35 species of reptiles were recorded in the APDC. Twenty percent of amphibians and 32% of registered reptiles are in some extinction risk category according to the Norma Oficial Mexicana NOM-059-SEMARNAT-2010, two amphibian species and one reptile species are included in the Red List of the International Union Conservation of Nature (IUCN), while 12% of reptiles are in high category of environmental vulnerability. The APDC has the highest species richness in comparison to the other two PPAs. Amphibians had a relatively similar composition among the PPAs, while for reptiles, species composition tended to be relatively different. Our results indicate that due to the richness of the species, the number of endangered species and species not evaluated by IUCN it harbors, the APDC contributes to the conservation of herpetozoa in a highly transformed area of southern Mexico, together with the two other PPAs, where the closest Protected Natural Area under governmental regime (Los Tuxtlas Biosphere Reserve) is located 50 km away.